2011
DOI: 10.1159/000327392
|View full text |Cite
|
Sign up to set email alerts
|

Language Specificity in Speech Perception: Perception of Mandarin Tones by Native and Nonnative Listeners

Abstract: The results reported in this paper indicate that native speakers of Mandarin Chinese rate the perceptual similarities among the lexical tones of Mandarin differently than do native speakers of American English. Mandarin listeners were sensitive to tone contour while English listeners attended to pitch levels. Chinese listeners also rated tones that are neutralized by phonological tone sandhi rules in Mandarin as more similar to each other than did English speakers – indicating a role of phonology in determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 56 publications
9
62
0
Order By: Relevance
“…As a result, there is a trade-off between response accuracy and RT in the native listeners' data. Huang and Johnson (2010), in a cross-linguistic study investigating tone perception by Mandarin and American English listeners, reported a similar finding: the RTs for some tone pairs (e.g., T35/T214) in Mandarin listeners' data were found to be significantly longer than those in American English listeners' data. Taken together, these results suggest that Taiwanese listeners process tones as contrastive linguistic categories, displaying some degree of categorical perception, whereas English listeners perceive tones in a more psychoacoustic way.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…As a result, there is a trade-off between response accuracy and RT in the native listeners' data. Huang and Johnson (2010), in a cross-linguistic study investigating tone perception by Mandarin and American English listeners, reported a similar finding: the RTs for some tone pairs (e.g., T35/T214) in Mandarin listeners' data were found to be significantly longer than those in American English listeners' data. Taken together, these results suggest that Taiwanese listeners process tones as contrastive linguistic categories, displaying some degree of categorical perception, whereas English listeners perceive tones in a more psychoacoustic way.…”
Section: Discussionmentioning
confidence: 56%
“…This language-specific perceptual difference exists even in the simple task of AX discrimination employed here (see also Huang and Johnson 2010). Taiwanese listeners were more accurate than English listeners in discriminating tone stimuli in both the T55-T33 and the T55-T51 continua.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This study builds to a lesser extent on Greenberg & Jenkins (1964) who compared only voiced stops and voiceless stops (see also Babel & Johnson 2010, Fleischhacker 2001, Huang 2004, Huang & Johnson 2010, Kato et al 1997 among others for studies using this paradigm to investigate knowledge of perceived similarity). In this experiment, native English listeners were presented with pairs of sounds minimally different in place, and were asked to judge the perceived similarity between the two sounds.…”
Section: Experiments I: Similarity Judgment Experimentsmentioning
confidence: 99%
“…This alternation in English may affect the similarity judgment of nasal minimal pairs; i.e., English listeners may judge nasal pairs to be similar, because they alternate with each other in their phonology (see e.g. Hume & Johnson 2003, Huang & Johnson 2010; though see also Steriade 2003). However, using English listeners may not be problematic for three reasons.…”
Section: Participantsmentioning
confidence: 99%